Eye-Hand Coordination and Agility with Basketball Lay-Up Skills: A Correlation Study in Students - Didi Suryadi; Mikkey Anggara Suganda; Y Touvan Juni Samodra; Isti Dwi Puspita Wati; Rubiyatno Rubiyatno; Youssouf Haïdara; Ibnu Wahyudi; Eko Saputra (JUMORA: Jurnal Moderasi Olahraga, 2023)
The skill of laying up a basketball is one of the important techniques that plays a role in giving pounds or numbers in the game. Therefore, it is necessary to know aspects related to lay up skills. This study aims to prove the relationship between eye-hand coordination and agility with basketball lay-up skills. In this study, a quantitative descriptive approach was used with the correlation study method. The subjects in this study were male students of class VII SMP St. Francis of Assisi Pontianak, totaling 25 male students. Data analysis in this study was assisted by using SPSS Version 26. Results of eye-hand coordination research with lay-up skills showing a significance value of 0.000 > 0.05, there is a significant relationship between eye-hand coordination and lay-up skills in students. agility results with lay-up skills showing a significance value of 0.004 > 0.05, there is a significant relationship between agility and lay-up skills in students. Furthermore, eye-hand coordination and agility with lay-up skills show a significance value of 0.000 < 0.05, so there is a significant relationship. The conclusion is that eye-hand coordination and agility have a significant relationship to lay-up skills in students. Keywords : Agility, Basketball, Hand-Eye Coordination, Lay Up Skills